Gefitinib: an "orphan" drug for non-small cell lung cancer. (2nd November 2017) - Ziogas, Dimitrios C.; Liontos, Michalis; Kyriazoglou, Anastasios; Tsironis, Georgios; Bamias, Aristotelis; Dimopoulos, Meletios-Athanasios
ABSTRACT: Introduction : The discovery of sensitizing mutations in epidermal growth factor receptor (EGFR) and the rapid development of EGFR tyrosine kinase inhibitors (TKIs) have substantially changed the management of non-small-cell lung cancer (NSCLC), leading to a tailored therapeutic approach for patients with advanced EGFR-mutant NSCLC. Gefitinib is an EGFR-directed TKI, approved by U.S. Food and Drug Administration (FDA) for the first-line treatment of patients with metastatic NSCLC whose tumors harbor specific EGFR gene mutations, as detected by an FDA-approved test. Areas covered: Here, we will focus on the approval of gefitinib as an effective EGFR-directed TKI option, describing the drug development to its currently established use. In parallel, based on the latest evidence, we will present its efficacy and its toxicity profile on selected NSCLC patients harboring specific EGFR driver mutations and we will try to reply to all open questions about gefitinib administration. Expert opinion: Gefitinib in NSCLC is an example of a more personalized approach to cancer therapeutics, where understanding of the molecular background of the cancer led to the appropriate evaluation of the drug into a selected patient population.